Malaria and Anemia cause impairments in athletic performance of young female athletes even after 1,5 year of clinical healing - Cárdenas, R. N.; de Aquino Freire, I.; Pumariega, Y. N.; da Silva, V. F.; Pumariega Torres, C. S.; Valentim-Silva, J. R.; dos Santos Farias, E.; de Souza, D. O.; Tada, M.; Stabeli, R. G. (International Journal of Sports Science, 2019)
Malaria is a vector-borne parasitic tropical disease found in 91 countries and produce high levels of blood-stage parasites, severe infarcts in critical organs, and anemia. This condition may cause impairments in physical performance and in the athlete health, moreover, data about the impact of the malaria and anemia in performance is sparse. So, the purpose here was evaluate the physical performance of female athletes with a history of anemia and malaria infection even after one and half year of clinical healing. Ten female athletes with malaria and anemia history (GAM) and ten without this history (GNM), had haematological, biochemical, and performance parameters assessed and statistically compared. To the endurance the GNM showed high VO2Máx 23.56+1.55 mL/Kg.min than GAM 19.19+2.64 (p= 0.0016). To the abdominal strength the GNM showed more strength 56.8+8.35 than GAM 39.1+6.93 (p=0.0007), regarding the score of the arm strength test it became evident that the GNM also showed more strength 24.4+5.91 than the GAM 17.9+4.1 (p=0.0003). Still in relation to the stretching test the GNM had best performance 40.9+4.04 as compared to the GAM 29.5+3.68 (p=0.003), and to the speed variable the GNM with 9.02+0.45 seconds also evidenced a better performance than the GAM with 9.45+0.53 seconds (p= 0.0002). In conclusion, the malaria and/or anemia history of the athletes investigated here proved to cause impairment in their physical performance even considering the fact the disease was acquired by them one and half year before they were admitted to the research.